Ethnic Diversity and Federalism : Constitution Making in South Africa and Ethiopia. - Fessha, Yonatan Tesfaye (Ashgate Pub., 2011)
The book examines how institutions of multi-ethnic states have been designed to accommodate ethnic diversity and maintain national unity. It locates institutional responses to the challenges of ethnic diversity within the context of a federal arrangement, examining how this has been used to reconcile the conflicting pressures of the demand for the recognition of distinctive identities, and the promotion of political and territorial integrity.